2007
DOI: 10.1002/cncr.22896
|View full text |Cite
|
Sign up to set email alerts
|

C‐reactive protein is an informative predictor of renal cell carcinoma‐specific mortality

Abstract: BACKGROUND. C‐reactive protein (CRP) represents a promising prognostic variable in patients with sporadic renal cell carcinoma (RCC). It was hypothesized that CRP can improve the prognostic ability of standard RCC‐specific mortality (RCC‐SM) predictors in patients treated with nephrectomy for all stages of RCC. METHODS. Radical nephrectomy was performed in 314 patients from 2 European centers. Life table, Kaplan‐Meier, and Cox regression analyses addressed RCC‐SM. Covariates included age, gender, TNM stage, tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(121 citation statements)
references
References 28 publications
4
116
0
1
Order By: Relevance
“…43 Absolute preoperative CRP as a continuous variable is also a good predictor of metastasis and mortality 1 year after surgery in clinically localized RCC patients. 44 The prognostic significance of CRP has been shown with its power for improving the combined predictive accuracy of established markers and prediction models through multivariable statistics 46,47 in a manner consistent with a criterion proposed by Kattan. 58 In a study by Karakiewicz et al that included 314 patients with any stage of RCC, CRP improved the predictive accuracy by 3.7% for RCC-specific mortality.…”
Section: Prognostic Value Of Crp In Renal Cell Carcinomamentioning
confidence: 67%
“…43 Absolute preoperative CRP as a continuous variable is also a good predictor of metastasis and mortality 1 year after surgery in clinically localized RCC patients. 44 The prognostic significance of CRP has been shown with its power for improving the combined predictive accuracy of established markers and prediction models through multivariable statistics 46,47 in a manner consistent with a criterion proposed by Kattan. 58 In a study by Karakiewicz et al that included 314 patients with any stage of RCC, CRP improved the predictive accuracy by 3.7% for RCC-specific mortality.…”
Section: Prognostic Value Of Crp In Renal Cell Carcinomamentioning
confidence: 67%
“…A study included 199 patients with unresectable pancreatic cancer showed the elevated CRP concentration was independently associated with overall survival (OS) (p=0.027) (Pine et al, 2009). And Karakiewicz (Karakiewicz et al, 2007) found that CRP was a predictor of renal cell cancer-specific mortality (p=0.003). Similar results were also found in gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, systemic Prognostic Significance of C-Reactive Protein in Urological Cancers: a Systematic Review and Meta-analysis improving the combined predictive accuracy. Karakiewicz et al reported CRP improved the predictive accuracy by 3.7% for CSS including 313 patients with any stage of RCC (Karakiewicz et al, 2007). And this prognostic effect for survival not only significant in localized but also in advanced metastatic RCC.…”
Section: Discussionmentioning
confidence: 92%
“…A total of 43 eligible studies (7, 490 patients) were identified for this meta-analysis (25 for RCC (Atzpodien et al, 2003;Bromwich et al, 2004;Casamassima et al, 2005;Peccatori et al, 2005;Ito et al, 2006;Lamb et al, 2006;Vogl et al, 2006;Karakiewicz et al, 2007;Komai et al, 2007;Ramsey et al, 2007;Kawata et al, 2008;Ramsey et al, 2008;Tanaka et al, 2008;Iimura et al, 2009;Jagdev et al, 2010;Cho et al, 2011;Falkensammer et al, 2011;Bedke et al, 2012;Fujita et al, 2012;Sim et al, 2012;Steffens et al, 2012;de Martino et al, 2013;Yasuda et al, 2013), 10 for UC (Hilmy et al, 2005;Hilmy et al, 2006;Saito et al, 2007;Yoshida et al, 2008;Gakis et al, 2011;Saito and Kihara, 2011;Ishioka et al, 2012;Obata et al, 2012;Tanaka et al, 2012;Stein et al, 2013), and 8 for PC (McArdle et al, 2006;Beer et al, 2008;Nakashima et al, 2008;McArdle et al, 2010;Pond et al, 2012;Prins et al, ...…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%